Mechanistic Understanding of Low κ Organosilicate Glass Film Planarization. (1st January 2019) - Mallikarjunan, Anupama; Achtyl, Jennifer; Yang, Rung-Je; Huang, Chen-Yuan; Chao, Shih-Hsuan; Gan, Lu; Tamboli, Dnyanesh; Ridgeway, Robert; Schlueter, James; Tsai, Ming-Shih; Li, Chris; O'Neill, Mark
Abstract : Low κ Organosilicate Glass (OSG) films are being proliferated into new IC device architectures. This study aims to understand the relationship between OSG film properties (both bulk and surface) and their removal rates (RR), and to develop a slurry that planarizes all OSG films at similar rates. Seven OSG films (κ ∼ 3, varying carbon content and elastic modulus) were polished along with TEOS oxide using an advanced barrier slurry. Counterintuitively, higher mechanical strength (i.e., elastic modulus) of the low κ film did not result in lower polish rates. An inverse relationship was observed between RR and the bulk chemical bonding structure Si(CH3 )x /SiOx peak area ratio as determined by transmission infrared spectroscopy measurements). In addition, the OSG film's surface free energy post-polish varied systematically only with the film's Si(CH3 )x /SiOx ratio. Since higher slurry pH increases the Si-O hydrolysis rate, a second slurry was formulated at pH > 10. The second barrier slurry also used silica abrasive and contained the same organic low κ rate modulator. However, this slurry allowed planarization of all the films at a similar rate. Such a slurry is better suited for robust manufacturing, as removal will not be affected by differences in OSG film composition.